A comprehensive meta-analysis of the impacts of intensified drought and elevated CO2 on forage growth. (1st February 2023) - Liu, Wanlu; Liu, Lulu; Yan, Rui; Gao, Jiangbo; Wu, Shaohong; Liu, Yanhua
Abstract: Forage crops are used worldwide as key feed sources for dairy systems. However, their productivity and quality are limited due to intensified drought events, elevated carbon dioxide (CO2 ), and their interaction with climate change, with consequences for the security of animal husbandry and the agricultural economy. Although studies have quantified the impacts of such stresses on forage growth, these impacts have been less systematically investigated in a global context due to differences among various forage groups, regional microclimates, and environmental factors. Herein we employed nine forage growth-related variables involving three perspectives, i.e., photosynthetic parameters, production, and quality, from research articles published between 1990 and 2021 via a meta-analysis. A linear mixed-effect model was then used to explore the quantitative relationship between these factors in a restricted dataset. Decreasing trends in all four photosynthetic parameters were detected across different eco-geographical regions with increasing drought stress. The maximum decrease in DMY occurred in the Mediterranean, with 52.8% under drought conditions. Globally, eCO2 significantly increased photosynthetic rate ( P n ) and instantaneous water use efficiency (WUEi ) by 40.8% and 62.1%, respectively, which also had positive effects on forage dry matter yield (DMY) (+25.1%), especially for forage in Northern Europe. However, this stress would significantly decrease forage quality by decreasing crude protein (CP) (−19.7%) and nitrogen content (N content) (−13.5%). These negative impacts would be aggravated under the co-occurrence of drought and eCO2, including a significant increase in WUEi (+111.1%) and a decrease in DMY (−12.3%). Gramineae showed a more sensitive response to drought stress in photosynthetic parameters and DMY than Leguminosae, but the latter exhibited a better response in photosynthetic parameters and production under eCO2 . Our analysis provides a consensus concerning how the growth parameters of forage have changed under environmental stresses. Highlights: A meta-analysis of impacts of climate change on forage growth-related variables. Both quality and production of forage are hampered by increasing drought stress. eCO2 concentration positively affects forage photosynthesis and quality. eCO2 can offset the loss of photosynthetic parameters and production under drought. Forage across eco-geographical regions shows different responses to climate change.